Design Of Dipole Microstrip Antenna With Cohen-Minkowski Fractal For 433 433 Mhz Frequency - Isman Wahyudi (IHSA Institute, 2020)
This final project discusses the design of a dipole microstrip antenna with Cohen-Minkowski fractals for a frequency of 433 MHz which can be applied to Industrial, Scientific, and Medical (ISM) Band channels. The microstrip antenna uses a substrate made from FR-4 with a thickness of 1.6 mm and a channel impedance of 75 . Antenna design and simulation using AWR Microwave Office 2004 Software.The results of the design using the Cohen-Minkowski fractal can minimize the antenna size by 29% iteration-1, and 40% iteration-2 so as to give a VSWR value of 1.02 for the dipole without iteration, 1.74 for the iteration-1 fractal dipole, and 1, 26 iterations of fractal dipoles. The return loss resulting from the antenna design is -37.7 for the dipole without iteration, -11.29 for the iteration-1 fractal dipole, and -18.69 for the iteration-2 fractal. Then the gain obtained from the antenna design is 4.78 dB for the dipole without iteration, 4.91 dB for the iteration-1 fractal dipole, and 4.78 dB for the iteration-2 fractal dipole. The radiation pattern generated from the antenna is unidirectional.